The European Union and emerging powers in the 21st century how Europe can shape a new global order - Renard, Thomas; Biscop, Sven (Ashgate Pub., 2012)
This book analyses the shifts in the structure of global power and examines the threats and opportunities they bring to Europe. Leading European Contributors reflect on how the EU can utilise collective strength to engage and compete with rapidly developing nations. They examine perceptions of the EU among the emerging powers and the true meaning and nature of any strategic partnerships negotiated. Finally they explore the shape and structure of the international system in the 21st century and how the EU can contribute to and shape it.